Perancangan Enterprise Architecture menggunakan TOGAF ADM untuk Integrasi Teknologi Informasi - M. Rudi Fanani (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2024)
Information systems and technology have many important roles for higher education, such as improving quality to support operations, management and decision-making functions. Most of the information systems currently available are not widely available and are not yet integrated with each other. One of them is within the Faculty of Science and Technology (SAINTEK). An information technology integration service is needed to meet user needs in accessing, using, and utilizing information systems. The Open Group Architecture Framework (TOGAF) is a framework for enterprise architecture that provides a comprehensive approach to planning, designing, and implementing enterprise information architecture, adopting 5 phases of the 10 existing phases, namely, Preliminary Phase, Architecture Vision, Business Architecture, Information System Architecture, and Technology Architecture the results of this research are architectures from these 5 phases so that they can provide an overview and ease of information technology integration.